2022
DOI: 10.3390/biom12101407
|View full text |Cite
|
Sign up to set email alerts
|

Ligands for Melanocortin Receptors: Beyond Melanocyte-Stimulating Hormones and Adrenocorticotropin

Abstract: The discovery of melanocortins in 1916 has resulted in more than 100 years of research focused on these peptides. Extensive studies have elucidated well-established functions of melanocortins mediated by cell surface receptors, including MSHR (melanocyte-stimulating hormone receptor) and ACTHR (adrenocorticotropin receptor). Subsequently, three additional melanocortin receptors (MCRs) were identified. Among these five MCRs, MC3R and MC4R are expressed primarily in the central nervous system, and are therefore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 242 publications
(330 reference statements)
0
7
0
Order By: Relevance
“…[34][35][36][37] MC3R and MC4R are predominantly expressed in the CNS, and are hence known as neural MCRs. 2 Their alpha-helical TM3 domains include cysteine at the C terminus and have a conserved pattern of aspartic acid-arginine-tyrosine in the junction. 38 The genes for human MCRs are found on autosomal single exons.…”
Section: The Mcrsmentioning
confidence: 99%
See 4 more Smart Citations
“…[34][35][36][37] MC3R and MC4R are predominantly expressed in the CNS, and are hence known as neural MCRs. 2 Their alpha-helical TM3 domains include cysteine at the C terminus and have a conserved pattern of aspartic acid-arginine-tyrosine in the junction. 38 The genes for human MCRs are found on autosomal single exons.…”
Section: The Mcrsmentioning
confidence: 99%
“…137 Preclinical studies suggest that the melanocortin system may act as a physiological protector in a number of acute and chronic neurodegenerative diseases 16,138 (Figure 4), and targeting the melanocortin system may induce both neuroprotection and neurogenesis. 23 It has been demonstrated that activating the MC4R in astrocytes has strong anti-inflammatory and in vitro neuroprotective effects, indicating that this may be a possible target to reduce continuing neurodegeneration and inflammation in MS. 2 Research showed that setmelanotide, as a highly selective and novel MC4R agonist, improves the reactive phenotype in astrocyte cells and significantly increases the production of interleukin-6 and −11. This effect may be caused by increased phosphorylation of CREB.…”
Section: The Therapeutic Potential Of the Melanocortin Systemmentioning
confidence: 99%
See 3 more Smart Citations